2021
DOI: 10.5812/semj.106559
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Extracorporeal Shockwave Therapy on de Quervain Tenosynovitis; a Clinical Trial

Abstract: Background: De Quervain tenosynovitis is mainly managed by conservative treatments, such as anti-inflammatory drugs, splint, and injection; however, surgical treatments are also recommended. Objectives: The present study aimed at assessing the efficacy of extracorporeal shockwave therapy in the treatment of de Quervain tenosynovitis. Methods: The current clinical trial was conducted on 26 patients with de Quervain tenosynovitis eligible for treatment. The intervention group received extracorporeal shock wave t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 34 publications
(37 reference statements)
0
13
0
Order By: Relevance
“…A total of 37 studies were initially found to be eligible. Of those, 7 studies did not include 1 of our predefined outcome measures or included patients with conditions other than DQT and did not analyze data separately and were therefore excluded (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of 37 studies were initially found to be eligible. Of those, 7 studies did not include 1 of our predefined outcome measures or included patients with conditions other than DQT and did not analyze data separately and were therefore excluded (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 17 studies were included in network meta-analyses, which were performed separately for short-term pain (15 studies; 14 interventions), mid-term pain (9 studies; 7 interventions), short-term function (8 studies; 7 interventions), and mid-term function (6 studies; 3 interventions). eFigures 17 through 20 in Supplement 1 show the comparative treatment class effects for short-term pain, mid-term pain, short-term function, and mid-term function.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations